History of fires and vegetation since the Neolithic in the Cantabrian Mountains (Spain). (19th February 2018) - Carracedo, Virginia; Cunill, Raquel; García‐Codron, Juan Carlos; Pèlachs, Albert; Pérez‐Obiol, Ramon; Soriano, Joan Manuel
Abstract: Fire has been one of the main causes of disturbance of vegetation over time, and since the Neolithic has become an irreplaceable tool for the opening of forest spaces and maintenance of pastures. Previous studies showed that the intensity and effects of wildfires are related to the biomass and controlled by climate factors. However, in regions such as Cantabria, where agriculture and livestock have spread throughout the territory since prehistory, fires should also be closely related to human land uses. The aim of this paper was to investigate the history of fires and vegetation since the Neolithic in the Cantabrian Mountains, using sedimentary charcoal and pollen data to study the role of human activities in the processes that have shaped ecosystems throughout the Holocene. The asynchrony and quantitative differences in the results obtained at different sites indicate significant variations in fire patterns at regional scale since the Neolithic, although the type and size of each basin also had a strong influence on charcoal accumulation. Maximum values for charcoal accumulation rate at La Molina were observed between the Neolithic and the Bronze Age but occurred after about 3500 cal years BP at El Cueto de la Avellanosa. At El Sertal, low charcoal accumulation rate values were observed, probably because the sequence begins in a space that already had been cleared; the maximum values occurred during the most recent millennium. These data provide evidence that fire has been a key factor in forest retreat and in maintaining open landscapes since the Neolithic.